How do you simplify (4+sqrt50)-(3-sqrt(8)) (4+50)(38)?

2 Answers
Mar 31, 2018

=1+7sqrt2=1+72

Explanation:

sqrt50=5sqrt250=52 and sqrt8=2sqrt28=22

Equation becomes (4+5sqrt2)-(3-2sqrt2)(4+52)(322)

=4+5sqrt2-3+2sqrt2=4+523+22

=1+7sqrt2=1+72

Mar 31, 2018

(4+sqrt50)-(3-sqrt8)=1+7sqrt2(4+50)(38)=1+72

Explanation:

(4+sqrt50)-(3-sqrt8)(4+50)(38)

sqrt50=sqrt(25xx2)=sqrt25xxsqrt2=5sqrt250=25×2=25×2=52

sqrt8=sqrt(4xx2)=sqrt4xxsqrt2=2sqrt28=4×2=4×2=22

(4+sqrt50)-(3-sqrt8)=(4+5sqrt2)-(3-2sqrt2)(4+50)(38)=(4+52)(322)

=4+5sqrt2-3+2sqrt2=4+523+22

=(4-3)+(5sqrt2+2sqrt2)=(43)+(52+22)

=1+7sqrt2=1+72

(4+sqrt50)-(3-sqrt8)=1+7sqrt2(4+50)(38)=1+72